Associations Between Personality Functioning, Childhood Trauma and Non-adherence in Cardiovascular Disease: A Psychodynamically-Informed Cross-Sectional Study - Haller, Karl; Fritzsche, Stefan; Kruse, Irina; O’Malley, Grace; Ehrenthal, Johannes C.; Stamm, Thomas (Frontiers in Psychology, 2022)
Objective: Although treatment adherence and lifestyle changes significantly improve the prognosis of cardiovascular disease, many patients do not comply with clinician recommendations. Personality functioning appears to be of importance and is hypothesized to be superior to symptom-based measures in explaining individual differences in non-adherence. Methods: 194 cardiology inpatients (mean age = 70.6 years, 60% male) were assessed using self-report measures in a cross-sectional design. Patients were assessed using the short version of the Operationalized Psychodynamic Diagnosis Structure Questionnaire (OPD-SQS) to measure personality functioning, as well as the Childhood Trauma Screener (CTS), the Patient Health Questionnaire (PHQ-9) for symptoms of depression, and the Generalized Anxiety Disorder Scale-7 (GAD-7). To assess non-adherence we introduced a brief, novel scale. Results: Non-adherence correlated significant with personality functioning (r = .325), childhood trauma (r = .204) and depressiveness (r = .225). In a stepwise multiple regression analysis with socio-demographic variables inputted into the model, higher deficits in personality functioning, higher levels of childhood trauma, and male gender were associated with non-adherence (adjusted R2=.149, F(3,190) = 12.225, p < .01). Level of depressive symptoms, anxiety, age, education, and income showed no significant additional predictive value and were excluded from the model.